Budgeting in the United States - Blöndal, Jón R.. (OECD Publishing, 2003)
The budgetary process in the United States federal government is different from that in other OECD member countries. This is a consequence of the strict separation of powers that characterises the American constitutional system and of a long historical development in which new layers of institutional innovation were successively added to existing ones. The presidential budgetary process started to develop in the beginning of the previous century. Its first codification took place in the Budget and Accounting Act of 1921, which required that the President submit a budget for the government to Congress and created the Bureau of the Budget, now the Office of Management and Budget (OMB). In the 1970s, Congress changed its own budgetary process through the Congressional Budget and Impoundment Control Act of 1974, which created the Congressional Budget Resolution and established the Congressional Budget Office. Another layer of innovation was added during the 1980s with the aim of controlling the deficit. This began with the Balanced Budget and Emergency Deficit Control Act of 1985, commonly known as the Gramm-Rudman-Hollings Act, which in 1990 was fundamentally amended by the Budget Enforcement Act...